Fisher choice may increase prevalence of green turtle fibropapillomatosis disease - Stringell, Thomas B.; Clerveaux, Wesley V.; Godley, Brendan J.; Phillips, Quinton; Ranger, Susan; Richardson, Peter B.; Sanghera, Amdeep; Broderick, Annette C. (Frontiers in Marine Science, 2015)
Disease in wildlife populations is often controlled through culling. But when healthy individuals are removed and diseased individuals are left in the population, it is anticipated that prevalence of disease increases. Although this scenario is presumably common in exploited populations where infected individuals are less marketable, it is not widely reported in the literature. We describe this scenario in a marine turtle fishery in the Turks and Caicos Islands (TCI), where green turtles are harvested for local consumption. During a two-year period, we recorded the occurrence of fibropapillomatosis (FP) disease in green turtles (Chelonia mydas) captured during in-water surveys and compared it with that of turtles landed in the fishery. 13.4% (n=32) of turtles captured during in-water surveys showed externally visible signs of FP. FP occurred at specific geographic locations where fishing also occurred. Despite the disease being prevalent in the size classes selected by fishers, FP was not present in any animals landed by the fishery (n=162). The majority (61%) of fishers interviewed expressed that they had caught turtles with FP. Yet, 82% of those that had caught turtles with the disease chose to return their catch to the sea, selectively harvesting healthy turtles and leaving those with the disease in the population. Our study illustrates that fisher choice may increase the prevalence of FP disease and highlights the importance of this widely neglected driver in the disease dynamics of exploited wildlife populations.